BATAS GEOGRAFIS DAN BATAS SOSIAL : KETERKAITAN UNIT GEOGRAFIS DAN KONSTRUKSI SOSIAL, PELAJARAN DARI MALUKU - Adhuri, Dedi Supriadi (P2KK LIPI, 2003)
This article discusses the connection between territory and socio-cultural construction of the Mollucan. First, it concerns on the connection between spatial and socio-cultural construction of Muslim and Christians communtieis. In this regard, it argues that the spatial segregation between these two communities, to some extents, reflects or is associated with their socio-cultural differences. Of course, the apparent differences stemp from the fact that their religions are not the same. This means that all aspects of their live concern on religious belief and rituals must be different. Apart from this, Muslim communities in Maluku Tengah (Central Maluku) are considered as more devoted to tradition as they still speak the ?language of earth? (bahasa tanah, vernacular language), while the Christians are not. On the contrary, in Maluku Tenggara (Southeastern Maluku), it is the Christians who are regarded as more tighted by tradition as they still use lela (antique cannon), gong and traditional rituals on their marriage. Second, it demonstrates the political economy of sea territory. Referring to conflict over coastal boundaries between Sather and Tutrean villagers, I observe that control over sea territory is one of the indexes by which social boundary between the noble (mel-mel) and the commoner (ren-ren) are drawn. Thus, when there is a precedence contestation between these two social groups, defining coastal boundary is one of the contested issues. Reffering to other cases, conflicts triggered by lift-net (bagan) operation, I show how ethnicity defines ?otherness,? which, then used to exclude people from accessing a communal sea territory. Finally, I demonstrate how local leaders make use the practice of marine communal property rights (hak ulayat laut) as a political capital to win the position of the village leader (kelapa desa).